FAKTOR-FAKTOR YANG MEMPENGARUHI KEKALAHAN PASANGAN HERMAN ABDULLAH DAN AGUS WIDAYAT DALAM PEMILIHAN GUBERNUR RIAU PUTARAN I DI KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Muhammad Rendy Dorona; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the District Tapung Hulu Kampar regency. What problem formulation Influencing factors Defeat Pair Herman Abdullah and Agus Widayat (HA) in Riau Governor Selection Round 1 in the District of Hulu Tapung Kampar Regency in 2013. The purpose of this study was to determine the factors that affect the cause of the defeat of the couple Herman Abdullah and Agus Widayat (HA) in the first round of election of the Governor of Riau in 2013 on 4 September 2013 in the district of Hulu Tapung and to know the strategic mistakes made successful teams Herman Abdullah , Data collection techniques that writers use consists of interviews, and documentation, this study used qualitative methods are described in the discussion of descriptive. Judging is based on research results from internal factors of lack of cooperation HA successful team in rallying public voice dikecamatan Tapung Huhu, this is due to lack of team success before with the community approach and successful team that is less known to the public dikecamatan Tapung Hulu, so that the vision and mission of the HA pair is not conveyed properly. Lack of coordination is done successful teams HA pair, where the less successful teams in coordination with community leaders and also the team leader of its own success, so places that are scheduled for the campaign was not implemented due to a conflicting schedule resulted in many people are disappointed. Lack of socialization is done either through the media or through the successful teams in the district Tapung Hulu, while the dissemination through the mass media more done in other districts, so that people in the district Tapung upstream felt less close and feel less attention by HA pair and external factors that mindset that people are easily influenced in particular by the views that should be changed that Tapung Hulu district community leader who had expected a figure of participation and socialization of the high life in order to realize an area with good again. Keyword : Governor Elaction, Tapung Hulu, And Herman Abdullah